COMPARISON OF STEROIDS TO NSAIDS, AND OTHER FORMS OF ANALGESIA IN THE MANAGEMENT OF POST-CHIKUNGUNYA ARTHRITIS - Hamza Alam (Army Medical College Rawalpindi, 2021)
Objective: To compare steroids with other treatment options like NSAIDS and other analgesics for management of postchikungunya arthritis based on visual analogue scale (VAS).